Short-term outcomes of non-operative management of blunt splenic injury: a retrospective study - Q. H. Nguyen; T. K. Dang; S. X. Hoang (Сеченовский вестник, 2025)
Aim. To evaluate the short-term outcomes of non-operative management (NOM) for blunt splenic trauma and to identify prognostic factors for its success at a tertiary hospital.Methods. The study cohort comprised 136 patients with blunt splenic rupture treated at People’s Hospital 115, Ho Chi Minh City, Vietnam, between January 2021 and December 2023. Non-operative management was implemented in 91 cases (66.9%). Collected data included demographics, injury characteristics, therapeutic interventions, complications and NOM outcomes.Results. Among the 91 patients who received NOM, the median age was 34 (25; 47) years with male-to-female ratio of 6:1. Traffic accidents accounted for most splenic ruptures (81.3%). Clinical symptoms included abdominal pain (98.9%) and distension (27.5%). Abdominal computed tomography findings according to the American Association for the Surgery of Trauma (AAST) classification revealed predominantly Grade II (30.8%) and Grade III (38.5%) splenic injuries. The hemoperitoneum volume correlated significantly with injury severity (p = 0.029). NOM was successful in 88 patients (96.7%), whereas three patients (3.3%) required splenectomy. The median hospital stay was 5 (4; 6) days. The median amount of blood transfusion was 937.5 ± 340.9 ml. No mortality was reportedConclusions. Our findings confirm that NOM should be considered as a first-line therapy for hemodynamically stable patients with blunt splenic injury, as it safely obviates the need for surgery while avoiding operation-associated morbidity.